Applying the principles of Matteo Ricci’s memory palace technique - Barli Bram; Aditya Agung Sutono; Tabita Hermayani (Politeknik Negeri Bali, 2020)
Vocabulary mastery is a crucial factor in language learning and it can be problematic for bilingual young learners of the preoperational stage. Matteo Ricci, a Jesuit missionary to China, was able to teach Chinese by using and developing an ancient mnemonic method called the memory palace technique, which then became a widely recognized language learning technique. The current researchers sought to discover whether or not the principles of Matteo Ricci’s memory palace technique were still relevant to today’s language learning context and applicable in designing English vocabulary learning media. The present research focused on the detailed aspects of the technique and to the guiding principles of educational media to learn English vocabulary items. The current research produced a prototype for a set of vocabulary learning media that could later be implemented, tested, evaluated and developed by other instructors and future researchers interested in the subject.